Analisis Kemampuan PjBL STEM Berbasis Gender pada Pembelajaran Pencemaran Lingkungan - Al-Idrus, Syarifa Wahidah; Rahmawati, Rahmawati (Chemistry Education Practice, 2024)
This research aims to determine the comparison of the implementation of PjBL with the STEM model based on gender. The type of research used is a One-Shot Case Study, namely an experiment carried out without a comparison group. All groups were given learning using PjBL STEM. The STEM aspects observed in this research are aspects of science (S), science–technology (S–T), science–engineering (S–E), and science–mathematics (S–M). The data collection method uses a series of questionnaires and tests. Data analysis uses N-gain to see an increase in learning outcomes regarding environmental pollution material. The research results show that STEM applications are not influenced by gender. It can be seen that student learning outcomes have increased with average N_gain of 0.92 and 0.83 respectively (high category).